DISCORDANT HARMONIES: A Fault line in Leibnizian Cosmology? - Hunter, Graeme (Science et Esprit, 2024)
Leibniz has several ways to account for the infinite number of actual things. They may exist because God, by “fiat,” brings them all into existence as secondary causes. Or they may all exist because they belong to the best possible world (BPW) which contains every entity compossible with every other entity. Or they may exist because God, like a craftsman, creates every being compossible with all he has already created, or means to create and install, in the BPW. It is not clear that these three accounts of the ultimate origin of things are compatible. The purpose of this essay is to show that they may be.